Comparison of the effects of bariatric surgery and pelvic floor muscle training on urinary incontinence in elderly women with obesity - Peng, Hui; Xian, Yunxian; Zhang, Jie (Surgery in practice and science, 2025)
Objective: To evaluate the effectiveness of BS in improving UI among elderly obese women and compare it to pelvic floor muscle exercises (PFME). Methods: This retrospective case-control study included 46 women diagnosed with UI, all patients underwent laparoscopic sleeve gastrectomy. These patients were compared to a matched cohort of 46 women who performed PFME and 92 control women who received no intervention. The primary outcome was assessed using the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF). Secondary outcomes included UI rehabilitation and sleep quality, measured by the Pittsburgh Sleep Quality Index (PSQI). Statistical analyses included univariate and multivariate logistic regression. Results: Both the BS and PFME groups showed significant improvements in UI and sleep quality compared to the control group. The PFME group had the best UI outcomes, with most participants reporting ICIQ-SF scores between 1 and 7 at 12 months. The BS group reported scores between 7.1 and 14, while the control group had scores mostly above 14.1. Postoperative complications, particularly diarrhea, significantly impacted the effectiveness of UI improvement in the BS group. Conclusion: Bariatric surgery can effectively improve UI in elderly obese women, although its impact is not as significant as PFME. Postoperative diarrhea is a risk factor that reduces the effectiveness of UI improvement after BS. Further research through multicenter, long-term, large-scale randomized controlled trials is recommended to validate these findings and explore the relationship between mental and physical conditions and UI improvement post-BS.